Effect Evaluation of Nanosilica Particles on O/W Emulsion Properties. (24th May 2022) - Qu, Guanzheng; Su, Jian; Shi, Tao; Guo, Rui; Peng, Jiao
Abstract : O/W emulsion reinforced by nanosilica particle has good application in hydrocarbon development. However, there are few reports on the influence of nanosilica particles on the oil-water interface of O/W emulsion. The effect of nanosilica particles on the interfacial properties of O/W emulsion was indirectly investigated by measuring the interfacial properties between aqueous dispersion of nanosilica particles and kerosene, and the properties of O/W emulsion reinforced by nanosilica particle were studied. The results showed that the aqueous dispersion of nanosilica particles could significantly reduce the interface tension (with kerosene) by more than 50%, and the interface tension between the aqueous dispersion and kerosene decreased with the increase in nanosilica content. The aqueous dispersion of nanosilica particles could significantly change rock wettability. When the content of nanosilica particles increased from 0.1% to 0.7%, the contact angle decreased from 44.89° to 27.62°. The surface tension of O/W emulsion prepared by the aqueous dispersion of nanosilica particles and kerosene was among 25 mN/m~30 mN/m. The contact angle was also particularly small, with an average of about 20.00°, a minimum of 12.50°. The salts had little effect on the interface tension of emulsions but had a significant influence on the contact angle and its stability. Magnesium salt could reduce the three-phase contact angle and increase the hydrophilic properties of O/W emulsion, while calcium salt had the opposite effect. Calcium salt and magnesium salt could reduce the stability of the emulsion, and calcium salt had a greater influence. The oil-water stratification adding either calcium salt or magnesium salt was about 1 day~3 days earlier than that without salts. In the experiment, when the content of nanosilica particles was among 0.3%~0.7%, the viscosity of O/W emulsion increased with the increase in nanosilica particles. When the content was 0.9%, the viscosity suddenly decreased, and the extent of reduction was about 21.7%. The findings of this study can help for better understanding the application of nanosilica particles in O/W emulsion, giving some suggestions for the application of nanoparticles in hydrocarbon development.